Chaos and Order, a Complement or a Dilemma in Companies, an Analysis Based on Complexity - Hidalgo-Flor, Roberto (2022)
Based on the principles for understanding complexity proposed by Edgar Morin, the article analyzes the relationship of companies with elements of the environment and the society that they are part of. This is necessary because the traditional, functionalist approach limits the analysis of what happens and what companies can do to manage their reality and their interrelationships. The purpose of the research is therefore to study and understand the environment that affects companies and their reciprocal influences, based on the paradigm of complexity. The applied methodology corresponds to a purely qualitative research, with in-depth interviews with companies and stakeholders in the business environment (consultants), using qualitative content analysis. The study identifies how the eight characteristics or principles of complexity arise in the environment-companies relationship, which could be defined as an intermittence of chaos and order. However, the research shows that, in light of the complexity paradigm, this apparent chaos represents an option of complementarity, creation, and growth, in which disarray, order, and organization constitute a virtuous circle; but also, that each company, each person, eachsituation, each environment is unique and complex, and must be treated accordingly.